LA UNIVERSIDAD EN LA FORMACIÓN DE EMPRENDEDORES EMPRESARIALES Y EL APOYO EN LA CREACIÓN DE NUEVAS EMPRESAS - Pérez Palacios, Emma (2009)
The university must educate for the “Entrepreneurship”, this means not only to teach to form companies - fundamental element without a doubt - but must be understood and be worked from an ample, actitudinal sense, of development of competitions, abilities and skills that allow a greater generation and advantage of the opportunities that the market offers. This new approach requires of a great will of the university authorities and to have an ample vision of the new surroundings of the universities, since to the date it has not been exploded like an excellent strategy of differentiation.